2003
DOI: 10.1021/bi035098j
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis for the Selectivity of Benzotriazole Inhibitors of PTP1B

Abstract: Protein tyrosine phosphatase 1B (PTP1B) has been implicated in the regulation of the insulin signaling pathway and represents an attractive target for the design of inhibitors in the treatment of type 2 diabetes and obesity. Inspection of the structure of PTP1B indicates that potent PTP1B inhibitors may be obtained by targeting a secondary aryl phosphate-binding site as well as the catalytic site. We report here the crystal structures of PTP1B in complex with first and second generation aryldifluoromethyl-phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 32 publications
(42 reference statements)
1
79
0
Order By: Relevance
“…Similarly, efforts to identify differences between TCPTP and PTP-1B by enzyme kinetic analysis did not reveal any discernible differences between the two enzymes that could be exploited for inhibitor design to achieve selectivity (23). Furthermore, a structural comparison of the three-dimensional crystal structures of both enzymes did not reveal obvious determinants of selectivity within the active site region.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, efforts to identify differences between TCPTP and PTP-1B by enzyme kinetic analysis did not reveal any discernible differences between the two enzymes that could be exploited for inhibitor design to achieve selectivity (23). Furthermore, a structural comparison of the three-dimensional crystal structures of both enzymes did not reveal obvious determinants of selectivity within the active site region.…”
Section: Resultsmentioning
confidence: 98%
“…The activity of all enzymes was assayed with fluorescein diphosphate (FDP) as substrate as previously reported (23,26). Kinetic constants were obtained by fitting the observed rates of reactions to the Michaelis-Menten equation with the aid of the non-linear curve fitting software program, Grafit 4.0.10 (Erithacus Software Inc.).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, we have reported on the crystal structure of difluorobenzotriazole inhibitors complexed with PTP1B and found that the two fluorine atoms are within van der Waals distance of Phe 182 and that they are hydrogen-bonded to a water molecule that also interacts with the phosphonate, the side chain nitrogen of Gln 266 , and the main chain nitrogen of Phe 182 (25). Examination of the crystal structures of PTP1B revealed that helix ␣7 interacts with the rest of the enzyme through an extensive series of hydrogen bonds with helix ␣3 and loop ␤9 -␤10 ( Fig.…”
Section: Tablementioning
confidence: 55%
“…1). The DFMP group of Inhibitor 1 engages the phosphatase by extensive hydrogen bonding of the phosphonate with the PTP loop (24,25). The two fluorine atoms are within van der Waals distance of the phenyl side chain of Phe 182 and are hydrogen-bonded through a water molecule to the side chain nitrogen of Gln 266 and the main chain nitrogen of Phe 182 (26,27).…”
Section: Use Of Yeast To Identify Amino Acid Determinants Of Ptp1b Inmentioning
confidence: 99%